Minuman Fungsional Fermentasi Berbasis Limbah Kulit Kopi Arabica dengan Symbiotic Colony of Bacteria and Yeast (SCOBY) Saccharomyces cerevisiae - Dian Kresnadipayana; D. Andang Arif Wibawa; Mardhiva Indra Saputra; Mei Kresnawati; Levina Levina Nur Andini; Istiqomah Dwi Mayawati (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2022)
Anggrasmanis Arabica Coffee, Jenawi District, Karanganyar Regency is a variety of arabica coffee which is one of the leading commodities originating from the Jenawi highlands, Karanganyar. In the coffee trade, an important part of trading is the beans obtained by going through several stages of processing. During such processing, considerable waste is produced both in solid and liquid form. The largest coffee processing solid waste is pulp (coffee cherry peel). The dried coffee fruit skin (cascara) can be used as fertilizer and animal feed. This study aims to  utilize and maximize the antioxidant potential of raw materials for arabica dry coffee fruit peel waste (cascara) in Anggrasmanis Village, with the use of active dry yeast microbes,  namely Saccharomyces cerevisiae,  into fermented functional drinks that are of selling value and beneficial to health. .  In this study, cascara was processed into fruit juice in a ratio of 1% : 5% : 10% ( cascara : sugar : water ), the addition of yeast was carried out according to the dosage indicated on the yeast packaging (2 grams for 10 liters of the basic solution).  and in the fermentation process for 7 days .  The results of this study are in the form of fermented functional  drinks from cascara arabica with the product name "Cascha" with an ethanol / methanol content of 0.142% so that functional drinks from casacara meet the Indonesian National Standard (SNI).